2013
DOI: 10.1016/j.idairyj.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of various minerals, proteins and salts of organic acids on the principal steps of α-lactose monohydrate crystallisation

Abstract: To study the effects of whey constituents on lactose crystallisation, a model based on population balance and taking into account mutarotation was implemented. Outputs were the nucleation constants (B 0 , k n0) and the growth rate constants (kg 0 , g 0). Batch crystallisation of a lactose solution (70 g 100 g À1 water) was studied with and without addition of various organic acids, salts, galactose and proteins. Kinetics and crystal size distributions were monitored using refractometry and laser light scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Crystals larger than 50 lm were found at the end of crystallization for the control treatment. The work carried out in model solutions by Gernigon et al (2013) found that larger lactose crystals had been formed when sodium citrate was present. The present work has demonstrated how the addition of sodium citrate salt influenced lactose crystallization in whey concentrate which, unlike model solutions, has other constituents that influence crystallization, such as whey proteins, casein residues, and other present salts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystals larger than 50 lm were found at the end of crystallization for the control treatment. The work carried out in model solutions by Gernigon et al (2013) found that larger lactose crystals had been formed when sodium citrate was present. The present work has demonstrated how the addition of sodium citrate salt influenced lactose crystallization in whey concentrate which, unlike model solutions, has other constituents that influence crystallization, such as whey proteins, casein residues, and other present salts.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of salts or sucrose has been shown to influence lactose crystallization (Gernigon et al 2013). Certain calcium salts such as nitrate increase lactose solubility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gernigon et al . ; Li et al . ), no studies exist that probe whether the type of vat affects lactose crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have investigated lactose crystallisation and the drying of dairy products (Guerra-Hern andez et al 2002;Kelly 2006;Syrios et al 2011;Gernigon et al 2013;Li et al 2016), no studies exist that probe whether the type of vat affects lactose crystallisation. The aim of this study was to describe the rate of lactose crystallisation in concentrated whey using two different vats.…”
Section: Introductionmentioning
confidence: 99%